Qualitative Analysis of some Types of Neutral Delay Differential Equations - Helal, May Mohammed (Iraqi Journal of Science, 2021)
In this paper, we conduct some qualitative analysis that involves the global asymptotic stability (GAS) of the Neutral Differential Equation (NDE) with variable delay, by using Banach contraction mapping theorem, to give some necessary conditions to achieve the GAS of the zero solution.